From big data mining to technical sport reports: the case of inertial measurement units - Rojas-Valverde, D.; Gómez-Carmona, C. D.; Gutiérrez-Vargas, R.; Pino-Ortega, J. (BMJ Open Sport & Exercise Medicine, 2019)
The inertial measurement units (IMU) are instruments used to quantify the external load of athletes; they are increasingly common in assessing team and individual sports. This type of instruments has several sensors, such as accelerometers, gyroscopes and magnetometers; this allows access to a large amount of information and analysis possibilities. Due to the complexity of synthesising this data, it is necessary to create a flow for collecting, analysing and presenting the collected data in a simple way and present it as quickly as possible to the technical staff. This report aims to present new methods of reduction of the data and propose a new approach method for the analysis of the IMU`s outcomes.